The orexigenic effect of ghrelin is mediated through central activation of the endogenous cannabinoid system. - Kola, B; Farkas, I; Christ-Crain, M; Wittmann, G; Lolli, F; Amin, F; Harvey-White, J; Liposits, Z; Kunos, G; Grossman, AB; Fekete, C; Korbonits, M (2008)
INTRODUCTION: Ghrelin and cannabinoids stimulate appetite, this effect possibly being mediated by the activation of hypothalamic AMP-activated protein kinase (AMPK), a key enzyme in appetite and metabolism regulation. The cannabinoid receptor type 1 (CB1) antagonist rimonabant can block the orexigenic effect of ghrelin. In this study, we have elucidated the mechanism of the putative ghrelin-cannabinoid interaction. METHODS: The effects of ghrelin and CB1 antagonist rimonabant in wild-type mice, and the effect of ghrelin in CB1-knockout animals, were studied on food intake, hypothalamic AMPK activity and endogenous cannabinoid content. In patch-clamp electrophysiology experiments the effect of ghrelin was assessed on the synaptic inputs in parvocellular neurons of the hypothalamic paraventricular nucleus, with or without the pre-administration of a CB1 antagonist or of cannabinoid synthesis inhibitors. RESULTS AND CONCLUSIONS: Ghrelin did not induce an orexigenic effect in CB1-knockout mice. Correspondingly, both the genetic lack of CB1 and the pharmacological blockade of CB1 inhibited the effect of ghrelin on AMPK activity. Ghrelin increased the endocannabinoid content of the hypothalamus in wild-type mice and this effect was abolished by rimonabant pre-treatment, while no effect was observed in CB1-KO animals. Electrophysiology studies showed that ghrelin can inhibit the excitatory inputs on the parvocellular neurons of the paraventricular nucleus, and that this effect is abolished by administration of a CB1 antagonist or an inhibitor of the DAG lipase, the enzyme responsible for 2-AG synthesis. The effect is also lost in the presence of BAPTA, an intracellular calcium chelator, which inhibits endocannabinoid synthesis in the recorded parvocellular neuron and therefore blocks the retrograde signaling exerted by endocannabinoids. In summary, an intact cannabinoid signaling pathway is necessary for the stimulatory effects of ghrelin on AMPK activity and food intake, and for the inhibitory effect of ghrelin on paraventricular neurons.